2012
DOI: 10.1097/fbp.0b013e3283564dd9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long-term caffeine administration on depressive-like behavior in rats exposed to chronic unpredictable stress

Abstract: Chronic unpredictable stress (CUS) was used to study the effects of a long-term treatment with either caffeine (8 mg/kg, orally) or desipramine (DMI) (10 mg/kg, intraperitoneally) in Wistar rats. The CUS procedure was applied for 6 weeks. Animals underwent a 2-week drug-free CUS procedure. Drugs were administered for 4 weeks alongside the stress and both drug and stress were continued throughout the behavioral testing period. CUS-exposed rats showed depressive-like behavior with reduced weight gain, reduced co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 42 publications
3
35
0
1
Order By: Relevance
“…It is considered as the most valuable and stable model of depression in animals [7]. The results of the present study showed that rats subjected to a 7-week period of CUS exhibited depressive-like behaviour with reduced weight, low motor activity, increased defecation and reduced consumption of sucrose compared with the control group, in consistency with many previous reports [2,22,23]. The sucrose preference test is an indicator of anhedonia-like behavioural change [27].…”
Section: Discussionsupporting
confidence: 91%
“…It is considered as the most valuable and stable model of depression in animals [7]. The results of the present study showed that rats subjected to a 7-week period of CUS exhibited depressive-like behaviour with reduced weight, low motor activity, increased defecation and reduced consumption of sucrose compared with the control group, in consistency with many previous reports [2,22,23]. The sucrose preference test is an indicator of anhedonia-like behavioural change [27].…”
Section: Discussionsupporting
confidence: 91%
“…The prevention of different alterations caused by repeated stress by regular (not acute) caffeine consumption had been noted previously by others (36)(37)(38) and is in tight agreement with the inverse correlation between caffeine intake and the incidence of depression (5,6). Given that caffeine intake increases in stressed individuals (4), it is tempting to speculate that this increased intake may be a prophylactic antistress measure to normalize mood-related behavioral changes by normalizing synaptic functions via A 2A R blockade.…”
Section: Discussionmentioning
confidence: 64%
“…Orally administered inosine also reproduces this effect (Muto et al, 2014). Interestingly A 2A receptor gene deficiency and A 2A receptor antagonists, including caffeine, also have antidepressant-like effect in the FST and TST (El Yacoubi et al, 2003;Hodgson et al, 2009) as well as in the chronic unpredictable stress paradigm of depression (Pechlivanova et al, 2012).…”
Section: Purinergic Regulation Of Neuroinflammation In Cns Disordersmentioning
confidence: 95%